Development of a Simulated Intra-Abdominal Model and Visual Analog Scale to Assess Visual Clarity of Laparoscopes [37M]. (May 2018) - Palvia, Vijay; Gonzalez, Aaron Herrera; Richard, Vigh; Anasti, James
Abstract : INTRODUCTION: Visual clarity (VC) is vital in performing laparoscopic surgery. However, few studies provide a direct assessment of laparoscopic VC or techniques to improve VC. METHODS: A box was constructed of ¼ inch acrylic glass with opaque insulation. An attached humidified source was heated to give a constant 81% humidity at 36 degrees Celsius. A 10 mm laparoscope was inserted and positioned 8 cm distal to a laminated white card containing black 12 pitch font. Four standard still images of varying visual clarity were captured and designated VC1, VC2, VC3, and VC4. A 10 cm visual analog scale (VAS) was used to rate VC scores. The 0 cm mark indicated total visual obstruction and the 10 cm mark indicated perfect visual clarity. The performance of the VAS was determined by having observers rate the still images. The observers were blinded to the VC rating and number of standard images used. Intra-observer and inter-observer differences were calculated. RESULTS: Standard images were assessed in random fashion 4 times by each of the 4 independent observers (64 total readings). Observed means were calculated (VC1, 9.2 ± 0.57 cm; VC2, 7.4 ± 0.65 cm; VC3, 4.4 ± 0.65 cm; VC4, 1.4 ± 0.52 cm). All values differed from each other (p < .001). Inter-observer differences were < 0.54 ± 0.37 cm and intra-observer differences were < 0.35 ± 0.13 cm. CONCLUSION: Our novel simulation model applied a visual analog scale that can serve as a tool to compare various techniques utilized for improving laparoscopic visual clarity.